Evaluation of in vitro antagonism assays in the mycoparasitic fungus Clonostachys rosea - Olsson, Victor (SLU/Dept. of Forest Mycology and Plant Pathology, 2020)
Fungicide use is the dominant direct method to control fungal pathogens on crops in agriculture. While effective, excessive use of them can be harmful to biodiversity and lead to fungicide resistance in pathogen populations. Biocontrol is an alternative where natural antagonistic organisms, called biocontrol agents (BCA), are used to protect crops. One such BCA is the mycoparasitic fungus Clonostachys rosea which has a wide host range, including Fusarium graminearum, an important fungal path-ogen causing the disease fusarium head blight in cereals. One important challenge facing the use of biocontrol is finding cost-effective ways of identifying strains of BCAs that incorporate the desired attributes. The purpose of this project is to evaluate three different in vitro assays for evaluation of C. rosea’s antagonism against F. gra-minearum and to find if they correlate with previous climate chamber experiments that more accurately represent field conditions. Six different strains of C. rosea with differing levels of expected biocontrol efficacy were used. The results indicate that the assays used do no correlate well with the biocontrol potential of the tested strains. There was also some indication of variation in phenotypic expression when different growth media were used. These results have support in the literature as in vitro screening for BCAs have been shown to miss strains of organisms that proved to be effective under field conditions. Further optimization of these assays is suggested to determine whether they can be useful for screening purposes. Improved protocols of these assays could also serve as a cost-effective means to study variations in pheno-types, relevant to biocontrol, between strains as well as other attributes important for BCAs to be implemented in commercial uses.